2023
DOI: 10.3389/fcvm.2023.1114058
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and accuracy of coronary artery calcium score on virtual non-contrast images derived from a dual-layer spectral detector CT: A retrospective multicenter study

Abstract: Rationale and objectiveThis retrospective study was to evaluate the feasibility and accuracy of coronary artery calcium score (CACS) from virtual non-contrast (VNC) images in comparison with that from true non-contrast (TNC) images.Materials and methodsA total of 540 patients with suspected of coronary artery disease (CAD) who underwent a dual-layer spectral detector CT (SDCT) in three hospitals were eligible for this study and 233 patients were retrospectively enrolled for further analysis. The CACS was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recent studies have investigated, for example, the evaluation of patients after EVAR [ 15 ], quantification of epicardial adipose tissue [ 16 ] or the quantification of coronary artery calcium [ 8 , 17 , 18 ] based on VNC pc reconstructions with promising results. Regarding the latter, the calcium sensitivity of VNC pc ’s provides TNC-equivalent values without the need for transformation, as previously required for VNC conv -based calcium assessment [ 6 , 7 , 9 , 19 , 20 ]. Moving organs are always a challenge in medical imaging, because they are prone to artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated, for example, the evaluation of patients after EVAR [ 15 ], quantification of epicardial adipose tissue [ 16 ] or the quantification of coronary artery calcium [ 8 , 17 , 18 ] based on VNC pc reconstructions with promising results. Regarding the latter, the calcium sensitivity of VNC pc ’s provides TNC-equivalent values without the need for transformation, as previously required for VNC conv -based calcium assessment [ 6 , 7 , 9 , 19 , 20 ]. Moving organs are always a challenge in medical imaging, because they are prone to artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Using PCCT-derived image data, Sharma et al demonstrated that calcium scores calculated from VNC images were underestimated [ 35 ]. Also, in DECT, the calcium scores calculated from VNC reconstructions seemed to be lower than these calculated from the TNC reconstructions [ 36 , 37 ]. This is well in line with our findings, as the current study also showed significantly lower mean values measured in L1 in the VNC reconstructions compared to the TNC reconstructions.…”
Section: Discussionmentioning
confidence: 99%